Assistance to women in normal hospital delivery from the perspective of nursing: an integrative review (Research, Society and Development, 2022)
The objective was to know the scientific production about the assistance to women who have normal hospital delivery from the perspective of nursing. The study consists of an integrative literature review. Data collection was carried out in April 2021, in 5 different databases. After using pre-defined selection criteria, 17 articles were found. The studies included in this review were classified into two thematic categories: New practices in obstetric care x inappropriate and/or harmful practices and Perception of Nurse/Midwife/Midwifery and postpartum women about the care provided in normal delivery. It was found that the insertion of the nurse minimizes trauma and negative outcomes in the scenario of pregnancy and birth, with positive repercussions for the NB, the woman and the family. It is believed that care based on scientific evidence, the adoption of educational technologies mediated by obstetric nursing and even the construction of knowledge among women, provide opportunities for disruptions and reconstructions in current obstetric and neonatal care.